Synthesis, characterization, electrochemistry and VOC sensing properties of novel metallophthalocyanines with four cyclohexyl-phenoxyphthalonitrile groups - ÖZKAYA, ALİ RIZA; KAKI, ESRA HACER (ELSEVIER SCIENCE SA, 2013)
The precursor [4,4'-cyclohexylidenebis(2-cyclohexylphenoxyphthalonitrile)] 3 was prepared by the reaction of 4-nitrophthalonitrile 1 and 1,1-bis[3-cyclohexyl-4-hydroxyphenyl]cyclohexane 2 in dry DMF in presence of dry K2CO3. The mononuclear phthalocyanines 4-6 were obtained from compound 3 by addition of the corresponding metal salts [Co(OAc)(2)center dot 4H(2)O, Zn(OAc)(2)center dot 2H(2)O, Cu(OAc)(2)]. The new compounds were characterized by elemental analysis, IR, UV-vis, H-1 NMR and MALDI-TOF mass spectrometry techniques. The response and recovery behaviors, sensitivity and selectivity of the spin coated films to different organic vapors have been investigated by means of conductivity measurements. The effect of humidity on the VOC vapor detection of the Pc films was also investigated. It was observed that the initial film conductivities was strongly influenced from relative humidity but, humidity had practically very small influences on the response and recovery characteristics of the sensors. The results offer a potential application for such phthalocyanine derivatives for the detection of volatile organic compounds, even at room temperature. Electrochemical and in situ spectroelectrochemical measurements confirmed that Co(II) phthalocyanine displays both metal- and ligand-based one-electron redox processes, while Zn(II) and Cu(II) phthalocyanine complexes show only ligand-based one-electron redox processes. Cyclic voltammetry provided information on the position of the energy levels of the highest occupied and the lowest unoccupied molecular orbitals, and thus the electrochemical band gaps of the complexes. The results reflected the semiconducting nature of the complexes. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Phthlocyanine; Synthesis; Gas sensing; Electrochemistry; Ethanol; Carbon tetrachloride; HETERO-DINUCLEAR PHTHALOCYANINES; PHOTODYNAMIC THERAPY; THIN-FILMS; METAL-FREE